Experimental and Theoretical Insights into the Optical Properties and Intermolecular Interactions in Push‐Pull Bromide Salts. Issue 4 (17th April 2019) - Venkatesan, Perumal; Cerón, Margarita; Pérez‐Gutiérrez, Enrique; Castillo, Armando E.; Thamotharan, Subbiah; Robles, Fernando; Siegler, Maxime A.; Percino, M. Judith
Abstract: Experimental and theoretical insights into the nature of intermolecular interactions and their effect on optical properties of 1‐allyl‐4‐(1‐cyano‐2‐(4‐dialkylaminophenyl)vinyl)pyridin‐1‐ium bromide salts (I andII ) are reported. A comparison of optical properties in solution and in the solid‐state of the salts (I andII ) with their precursors (Ia andIIa ) is made. The experimental absorption maxima (λmax ) in CHCl3 is at 528 nm forI and at 542 nm forII, and a strong bathochromic shift of ∼110 nm is observed for saltsI andII compared with their precursors. The absorption bands in solid‐state at ∼627 nm forI and at ∼615 nm forII that are assigned to charge transfer (CT) effect. The optical properties and single crystal structural features ofI andII are explored by experimental and computational tools. The calculated λmax and the CT are in good agreement with the experimental results. The intermolecular interactions existing in the crystal structures and their energies are quantified for various dimers by PIXEL, QTAIM and DFT approaches. Three types of interactions, (i) the cation⋅⋅⋅cation interactions, (ii) cation⋅⋅⋅anion interactions and (iii) anion⋅⋅⋅anion interactions are observed. The cationic moiety is mainly destabilized by C−H⋅⋅⋅N/π and π⋅⋅⋅π interactions whereas the cation and anion moiety is predominantly stabilized by strong C−H⋅⋅⋅Br − interactions in both structures. The existence of charge transfer between cation and anion moieties in these structures is established through NBO analysis. Abstract : Inside the salt : Experimental and theoretical insights into the nature of optical, charge transfer and intermolecular interactions in 1‐allyl‐4‐(1‐cyano‐2‐(4‐(dimethylamino)phenyl)vinyl)pyridin‐1‐ium bromide salts (I andII ) are compared with their precursors (Ia–IIa ).